Exploring the attachment of the Mediterranean medicinal leech (Hirudo verbana) to porous substrates. Issue 168 (15th July 2020) - Kampowski, Tim; Thiemann, Lara-Louise; Kürner, Lukas; Speck, Thomas; Poppinga, Simon
Abstract : Haematophagous ectoparasites must ensure a reliable hold to their host during blood meals and, therefore, have evolved a broad spectrum of versatile and effective attachment mechanisms. The Mediterranean medicinal leech ( Hirudo verbana ), for example, uses suction on both smooth and textured air-tight substrates. However, preliminary studies showed that H. verbana is also capable of attaching itself to air-permeable substrates, where suction does not work. Using high-speed videography and mechanical tests, we comparatively investigated the attachment of H. verbana on both smooth and textured air-tight as well as on porous artificial substrates, also considering the influence of mucus on sucker surfaces. In general, the leech-specific locomotion cycle did not differ between the tested surfaces, and the leeches were able to reliably attach to both air-tight and porous substrates. From our results, we conclude that suction is presumably the primary attachment mechanism of H. verbana . However, secondary mechanisms such as mechanical interlocking with surface asperities and pores or capillary forces occurring at the interface between the mucus-covered suckers and the substratum are also employed. In any case, the rich repertoire of applicable attachment principles renders the organs of H. verbana functionally highly resilient.